A comparative study of the antiangiogenic activity of hydroxytyrosyl alkyl ethers - Marrero Capitán, Ana Dácil; Castilla, Laura; Espartero Sánchez, José Luis; Madrona, Andrés; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel; Martínez-Póveda, Beatriz Amparo (My University, 2020)
The phenolic compound hydroxytyrosol and its derivatives are responsible for some of the health benefits of the intake of virgin olive oil, having shown antiangiogenic properties. In this study, we explored the antiangiogenic potential of six synthetic hydroxytyrosyl alkyl ethers (HT C1, C2, C4, C6, C8 and C12). Our results showed that all compounds affected endothelial cell viability in vitro at low micromolar doses. In addition, compounds HT C1, C2, C4 and C6 inhibited endothelial cell migration and formation of tubular-like structures. In these assays, hydroxytyrosyl hexyl ether (HT C6) exhibited the most potent inhibitory activity in vitro, activating as well apoptosis in endothelial cells. Furthermore, the antiangiogenic activity of HT C6 was confirmed in vivo in the chick chorioallantoic membrane assay. Hence, we present hydroxytyrosol synthetic derivative HT C6 as a new antiangiogenic compound and as a good candidate for an antiangiogenic drug in the treatment of angiogenesisdependent diseases.
Versión preprint del manuscrito de los autores, publicado finalmente en: Food Chemistry 333 (2020) 127476 con DOI: 10.1016/j.foodchem.2020.127476
Keywords: Neovascularización; Aceite de oliva; Angiogenesis; Hydroxytyrosyl alkyl ethers; Extra virgin olive oil